2022
DOI: 10.3389/fonc.2022.878499
|View full text |Cite
|
Sign up to set email alerts
|

Development of a MRI-Based Radiomics Nomogram for Prediction of Response of Patients With Muscle-Invasive Bladder Cancer to Neoadjuvant Chemotherapy

Abstract: ObjectiveTo develop and evaluate the performance of a magnetic resonance imaging (MRI)-based radiomics nomogram for prediction of response of patients with muscle-invasive bladder cancer (MIBC) to neoadjuvant chemotherapy (NAC).MethodsA total of 70 patients with clinical T2-4aN0M0 MIBC were enrolled in this retrospective study. For each patient, 1316 radiomics features were extracted from T2-weighted images (T2WI), diffusion-weighted images (DWI), and apparent diffusion coefficient (ADC) maps. The variance thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The combined model reached an accuracy of 93% in terms of differentiating muscle invasion preoperatively. Finally, radiomic features have the potential of predicting neoadjuvant chemotherapy response, defined as ≤ pT1 on the pathological report from radical cystectomy ( 20 ). Based on aggressiveness patterns derived from T2WI, ADC and DWI, combined with clinical staging, the proposed nomogram reached sensitivity, specificity, and accuracy of 94.4%, 94.1% and 94.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The combined model reached an accuracy of 93% in terms of differentiating muscle invasion preoperatively. Finally, radiomic features have the potential of predicting neoadjuvant chemotherapy response, defined as ≤ pT1 on the pathological report from radical cystectomy ( 20 ). Based on aggressiveness patterns derived from T2WI, ADC and DWI, combined with clinical staging, the proposed nomogram reached sensitivity, specificity, and accuracy of 94.4%, 94.1% and 94.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, radiomics has become a popular method for preoperative prediction of bladder tumor pathology, thanks to advances in medical technology, and has achieved remarkable success in that regard. 12 , 17 , 18 , 19 Several researchers have applied CT, MRI, and ultrasound to radiomic studies for predicting histological grading and staging features of BLCA and have demonstrated good predictive efficacy. 20 , 21 However, in most studies, only predictive nomogram model that contained imaging features was constructed, and models for other histologies were not.…”
Section: Discussionmentioning
confidence: 99%
“…CT imaging has a fundamental role in the diagnosis, staging, treatment guidance, and response monitoring in BCa [ 3 ]. As imaging-based features can be easily obtained non-invasively at low costs, radiomics has been increasingly evaluated for initial detection, grading, and local as well as nodal staging of BCa patients [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ], for recurrence assessment [ 31 , 32 , 33 ] and for the response evaluation to neoadjuvant preoperative as well as adjuvant treatments in recent years [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. However, to our knowledge, no imaging-based machine-learning models have been investigated for outcome prediction of BCa patients before RC.…”
Section: Discussionmentioning
confidence: 99%